2017
DOI: 10.1039/c7py01431g
|View full text |Cite
|
Sign up to set email alerts
|

Force-induced cleavage of a labile bond for enhanced mechanochemical crosslinking

Abstract: We demonstrate a promising approach towards designing force-responsive polymers. A thiocarbonylthio group exhibits amplified mechanochemical activity, triggering healing via crosslinking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…The development of polymeric materials that feature functionalities capable of undergoing bond scission in response to an applied mechanical force ( i.e. , mechanophores) has led to exciting new findings, ranging from materials that toughen when damaged24,25 to the mechanically facilitated “unzipping” of a polymer backbone to yield a conducting polymer 26. The breadth of chemical functionalities that can be appended to mechanophores enables their incorporation into a variety of polymeric systems ( e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The development of polymeric materials that feature functionalities capable of undergoing bond scission in response to an applied mechanical force ( i.e. , mechanophores) has led to exciting new findings, ranging from materials that toughen when damaged24,25 to the mechanically facilitated “unzipping” of a polymer backbone to yield a conducting polymer 26. The breadth of chemical functionalities that can be appended to mechanophores enables their incorporation into a variety of polymeric systems ( e.g.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the former was demonstrated in four separate polymers each comprised of two types of monomers: one whose isomerization was accelerated by mechanical load, and the other that reacted spontaneously with the isomerization product to form the crosslinks [26–29] . Load‐induced polymerization was achieved when mechanical load generated a catalyst or initiator for polymerization of monomers dissolved in the material prior to loading [30–34] …”
Section: Methodsmentioning
confidence: 99%
“…[26][27][28][29] Load-induced polymerization was achieved when mechanical load generated a catalyst or initiator for polymerization of monomers dissolved in the material prior to loading. [30][31][32][33][34] Endowing polymers with both damage-signaling and selfreinforcing capacity requires either increasing the number of distinct components, which presents both synthetic challenges and the need to avoid cross-reactivity in a loaded material or creating dual mechanophores. These are reactive sites that are both mechanochromic and either initiate or catalyze polymerization of the dissolved monomers, or react stoichiometrically with complementary sites on adjacent chains for crosslinking.…”
mentioning
confidence: 99%
“…The conversion of mechanical energy into increased material strength or improved mechanical properties, such as that accomplished by biological muscles, would be ideal but remains challenging. Recently, self‐strengthening polymers that can form new chemical networks in response to mechanical stress have emerged in the spotlight [9–16] . For example, Craig et al.…”
Section: Figurementioning
confidence: 99%
“…Recently, self-strengthening polymers that can form new chemical networks in response to mechanical stress have emerged in the spotlight. [9][10][11][12][13][14][15][16] For example, Craig et al have achieved shear-induced crosslinking via the ring-opening reaction of gem-dibromocyclopropane and subsequent nucleophilic substitution reactions with a bifunctional carboxylate. [9] Gong et al have reported that double-network gels in a monomer solution demonstrated self-growing ability in response to stretching via radical polymerization and the formation of new polymer networks.…”
mentioning
confidence: 99%